Photoacoustic cavitation for theranostics: mechanism, current progress and applications. (November 2015) - Feng, Y; Qin, D; Wan, M
Abstract: As an emerging cavitation technology, photoacoustic cavitation (PAC) means the formation of bubbles in liquids using focused laser and pre-established ultrasound synchronously. Its significant advantages include the decreased threshold of each modality and the precise location of cavitation determined by the focused laser. In this paper, a brief review of PAC is presented, including the physical mechanism description, the classic experimental technology, the representative results in variety of media, and its applications in biomedical imaging and therapy. Moreover, some preliminary results of PAC in perfluoropentane (PFP) liquid and PFP droplets investigated by passive cavitation detection (PCD) in our group are also presented.